Effects of Different Doses of GEN-003, a Therapeutic Vaccine for Genital Herpes Simplex Virus-2, on Viral Shedding and Lesions: Results of a Randomized Placebo-Controlled Trial. (6th July 2018) - Van Wagoner, Nicholas; Fife, Kenneth; Leone, Peter A; Bernstein, David I; Warren, Terri; Panther, Lori; Novak, Richard M; Beigi, Richard; Kriesel, John; Tyring, Stephen; Koltun, William; Lucksinger, Gregg; et al.
Abstract : GEN-003 is a candidate therapeutic vaccine for herpes simplex virus type 2 (HSV-2). Immunization with GEN-003 antigen/MM2 adjuvant combinations of 60/50 µg and 60/75 µg produced significant reductions in HSV-2 viral shedding and lesion rates for up to 12 months. Abstract: Background: GEN-003 is a candidate therapeutic vaccine for genital herpes simplex virus type 2 (HSV-2). We compared virologic and clinical impact of varying GEN-003 doses. Methods: Adults with symptomatic HSV-2 received placebo or GEN-003 (30 or 60 µg antigen with 25, 50, or 75 µg adjuvant). Viral shedding and lesion rates before vaccination were compared with those measured immediately after vaccination, then at weeks 29–33 and 53–57 after last dose. Results: Compared with baseline shedding rates, the rate ratios for viral shedding immediately after treatment were as follows: 0.82 (95% confidence interval [CI], 0.49–1.36), 30 µg antigen/25 µg adjuvant (30/25) dose; 0.64 (95% CI, 0.45–0.92), 30/50 dose; 0.63 (95% CI, 0.37–1.10), 30/75 dose; 0.56 (95% CI, 0.36–0.88), 60/25 dose; 0.58 (95% CI, 0.38–0.89), 60/50 dose; 0.45 (95% CI, 0.16–0.79), 60/75 dose; and 0.98 (95% CI, 0.76–1.26), placebo. Lesion rate reductions by GEN-003 ranged from 31% to 69%, but lesion rates also decreased among placebo recipients (62%). Reductions in shedding and lesion rate were durable for 12 months for the 60 µg antigen plus 50 or 75 µg adjuvant groups. No serious adverse events occurred with vaccination. Conclusions: The most efficacious vaccine combinations for GEN-003 were the 60 µg/50 µg and 60 µg/75 µg doses.